The Impact Of Artificial Intelligence–Based Recruitment On Employee Performance And Organizational Fairness - Eli Retnowati; Heriswanto Heriswanto; Istiyawati Rahayu; Agus Suyatno (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study aims to analyze the impact of Artificial Intelligence (AI)–based recruitment on employee performance and organizational fairness through a systematic literature review approach. The rapid development of AI technologies has transformed recruitment practices by enabling data-driven decision-making, improving efficiency, and reducing human bias. However, the implications of these technologies for organizational outcomes remain a subject of debate. This study synthesizes findings from peer-reviewed journals, books, and reputable academic sources published between 2010 and 2025. The analysis focuses on three main aspects: the effectiveness of AI-based recruitment, its influence on employee performance, and its impact on organizational fairness. The results indicate that AI-based recruitment enhances the accuracy and efficiency of hiring processes, leading to improved person–job fit and potential increases in employee performance. However, its impact on performance is indirect and influenced by broader organizational factors such as leadership and organizational culture. In terms of fairness, AI systems promote procedural consistency but raise concerns regarding algorithmic bias and lack of transparency. These challenges may affect employee trust and perceptions of organizational justice. Therefore, the study concludes that while AI-based recruitment offers significant benefits, its implementation must be accompanied by ethical governance, transparency, and integration with human-centered HR practices to ensure sustainable organizational outcomes.